2007
DOI: 10.1080/14764170601134479
|View full text |Cite
|
Sign up to set email alerts
|

The current role of laser/light sources in the treatment of male and female pattern hair loss

Abstract: Over the past several years there has been great interest in the potential role of laser/light-based treatments for male and female pattern hair loss. Despite aggressive marketing and centers claiming great success in the treatment of hair loss there is little scientific data supporting laser/light sources in hair loss. This paper is a consensus of hair loss experts on the current scientific data, mechanisms of action, safety, protocols and recommendations regarding laser/light treatment for hair loss. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 12 publications
1
64
0
2
Order By: Relevance
“…Many physicians specializing in hair agree that more studies are needed to examine its role in treating hair loss. 178 Other vitamins, supplements, and products…”
Section: Low-level Light Therapymentioning
confidence: 99%
“…Many physicians specializing in hair agree that more studies are needed to examine its role in treating hair loss. 178 Other vitamins, supplements, and products…”
Section: Low-level Light Therapymentioning
confidence: 99%
“…In this context, it is important to note that several preclinical [3] and clinical studies [4,5] have demonstrated that exposure to low-level laser therapy has a positive influence on several hair growth parameters, such as hair tensile strength and hair counts. Though the observations of these studies are very encouraging, the scientific basis for the results has not been satisfactorily validated [6,7] . One factor contributing to this is the fact that monitoring the effect of a particular treatment regimen on hair follicles would generally require a skin biopsy and histological examination of serial skin sections, followed by manual or automated counting of hair follicles [8,9] .…”
Section: Introductionmentioning
confidence: 97%
“…The exact mechanism of photobiomodulation that stops or reduces hair loss in patients is not well known [85,89]. Low-level visible light treatment (LLLT) modulates the gen expression of 5α-reductase and vascular endothelial growth factor (VEGF) and consequently stimulates hair growth through androgen metabolism and angiogenesis [90].…”
Section: Androgenetic Alopeciamentioning
confidence: 99%
“…There is a consensus among many authors that current laser/light sources are safe methods if they can be used properly and also these treatment modalities can be used alone or in combination with other treatments. The literature reveals that the texture and quality of hair improves even if there is no hair regrowth by the use of laser/light sources [85].…”
Section: Laser and Light Sources In The Treatment Of Alopeciamentioning
confidence: 99%